2009
DOI: 10.1063/1.3104606
|View full text |Cite
|
Sign up to set email alerts
|

Orientational order of near D3h solutes in nematic liquid crystals

Abstract: Solutes that are similar in size, have a shape that is close to D(3h) symmetry but contain dissimilar substituent groups (methyl versus chloro, contributing different electrostatic interactions to the anisotropic intermolecular potential), are used to delineate the short- and long-range anisotropic intermolecular interactions that lead to solute orientational order in nematic liquid crystals. The short-range interactions should be similar for all solutes and for D(3h) symmetry should yield a single independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Although these models are based on shape and do not include specific intermolecular interactions, such as electrostatic interactions or hydrogen bonding, their general value and success has been established by their application to predict and interpret the experimental results for a wide variety of guest-host systems. 14,24,[28][29][30] The definition of the molecular frame is also crucial to computational studies of ordered systems because a principal molecular axis needs to be defined to calculate a molecular order parameter. Early molecular dynamics (MD) simulations of liquid crystal systems typically employed coarse-grain approaches in which molecules were described by single geometric entities, for which a principal molecular axis is readily defined as the principal symmetry axis.…”
Section: Introductionmentioning
confidence: 99%
“…Although these models are based on shape and do not include specific intermolecular interactions, such as electrostatic interactions or hydrogen bonding, their general value and success has been established by their application to predict and interpret the experimental results for a wide variety of guest-host systems. 14,24,[28][29][30] The definition of the molecular frame is also crucial to computational studies of ordered systems because a principal molecular axis needs to be defined to calculate a molecular order parameter. Early molecular dynamics (MD) simulations of liquid crystal systems typically employed coarse-grain approaches in which molecules were described by single geometric entities, for which a principal molecular axis is readily defined as the principal symmetry axis.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, various theoretical models have been proposed for rationalizing the experimental observations; however, none of these has prevailed, and there are still unanswered questions. A large number of studies ,,,, have tried to relate specific molecular features (structure, electric multipoles, shape, surface, polarizability) to the orientational order of the host liquid crystal (LC). Unfortunately, an unavoidable problem in analyzing real experimental data with the aim of assessing the relative importance of the various types of interactions is that all the contributions to the intermolecular energy are superimposed and cannot be easily separated.…”
Section: Introductionmentioning
confidence: 99%
“…The surface tensor model is based on readily calculated molecular surfaces, but is also reliant on the use of an appropriate value of the orienting strength of the host, e, in eqn (7), which is typically fitted to provide an optimum match between calculated and experimental data. 35,43,56,[79][80][81] The premise of the work reported here is to present and assess a method for calculating order parameters of hypothetical structures, thus precluding a value of e being fitted to experimental data from the dyes being studied. An alternative approach is to use a value of e that has been shown to be appropriate for nematic hosts in general, although such a value would inevitably be more appropriate for some hosts than others, and any systematic discrepancy between calculated and experimental order parameters would primarily be attributed to the value used for e. Hence, it is desirable to be able to derive a value of e that is specific to the host being studied without relying on experimental data from a range of dyes within that host.…”
Section: Surface Tensor Modelmentioning
confidence: 99%
“…43 In neutral (uncharged) guest-host systems the first term of this expansion may be neglected, but the second two terms have been the subject of significant research. Early work suggested that molecular dipoles are of little importance to molecular alignment, 48 but later work has been divided, with some studies agreeing, [49][50][51] and others suggesting this may not be the case. [52][53][54] The interaction between molecular quadrupoles and an electric field gradient arising from the host has been extensively studied, and there is a significant body of work showing a close match between experimental and calculated orientational order parameters using a quadrupole term in the expression for the orientational energy, 37,44,49,50,[55][56][57] Although alternative mean-field treatments of electrostatic interactions have been proposed, 58,59 the quadrupole interaction remains one of the most widespread.…”
Section: Introductionmentioning
confidence: 99%